Decision Support System for Home Selection in South Tangerang City Using TOPSIS Method - Haris Widjaja; Ririn Ikana Desanti (IJNMT (International Journal of New Media Technology), 2020)
The desire to have a dream house makes people consider of the criteria of the house they will be lived. Many developers offer a variety of house alternatives ranging from price, location, design, building area and land area. Customers are pleased to choose their dream house as their desired. Based on that situation, this research is conduct to create a web-bases application for home selection that consider the useful criteria to help consumers choose a decent home by using the Technique for Order of Preference by Similarity To Ideal Solution (TOPSIS) method. The TOPSIS method has the concept that the best alternative has the shortest distance from a positive ideal solution and also has the farthest distance from a negative ideal solution. This TOPSIS method is applied to provide recommendations on the choice of home decisions in the South Tangerang area based on predetermined criteria. The results obtained in the TOPSIS calculation are the housing recommendations that are closest to the value of the calculation result.